Effects of once-daily darunavir/ritonavir versus atazanavir/ritonavir on insulin sensitivity in HIV-infected persons over 48 weeks: results of an exploratory substudy of METABOLIK, a phase 4, randomized trial. Issue 2 (3rd March 2016) - Overton, Edgar Turner; Tebas, Pablo; Coate, Bruce; Ryan, Robert; Perniciaro, Amy; Dayaram, Yaswant K.; De La Rosa, Guy; Baugh, Bryan P.
Abstract : Background : The phase 4, METABOLIK trial demonstrated that changes in metabolic parameters with darunavir with low-dose ritonavir (DRV/r) were comparable to those observed with atazanavir with low-dose ritonavir (ATV/r). A comprehensive assessment of the effects of these agents on insulin sensitivity will provide additional, relevant clinical information. Methods : In this substudy of METABOLIK, HIV-1–infected, antiretroviral agent–naïve male subjects aged ≥18 years with a viral load of >1, 000 copies/mL were randomized to receive DRV/r 800/100 mg once daily (qd) or ATV/r 300/100 mg qd, both with a fixed dose of tenofovir disoproxil fumarate/emtricitabine 300/200 mg qd. The effects of DRV/r versus ATV/r on insulin sensitivity over 48 weeks were compared using the euglycemic hyperinsulinemic clamp, the preferred method to assess insulin sensitivity; primary end point was the effect on insulin sensitivity during the first 12 weeks. Results : Twenty-seven subjects completed the study. In the DRV/r arm ( n = 14), median glucose disposal from baseline through weeks 12 and 48 was 9.3, 11.4, and 9.9 mg/kg*min, respectively; in the ATV/r arm ( n = 13), these values were 8.9, 8.6, and 9.1 mg/kg*min, respectively. Median insulin sensitivity in the DRV/r arm at baseline, week 12, and week 48 was 24.0, 25.0, and 21.5 mg/kg*min per μIU/mL × 100, respectively; these values in the ATV/r arm were 20.7, 22.0, and 22.0 mg/kg*min per μIU/mL × 100, respectively. Most subjects had ≥1 adverse event, including three serious adverse events ( n = 2 [DRV/r], n = 1 [ATV/r]). Conclusions : DRV/r and ATV/r displayed similar modest effects on insulin sensitivity using a euglycemic hyperinsulinemic clamp.